Macrosomia fetal - Siguenza Balladares, Nicole Elizabeth; Suarez Pelaez, Karla Vanessa (Machala : Universidad Técnica de Machala, 2020)
Introduction: Fetal macrosomia is considered the most frequent complication related to gestational diabetes, with a high morbidity rate. According to the worldwide incidence, this alteration represents 15 to 45% of newborns of diabetic mothers. macrosomic is considered to be all neonates whose birth weight is> 4000 g, that is, their weight is equal to or greater than the 90th percentile according to their gestational age. The present investigation is a clinical case study in a patient who has had diabetes mellitus for 1 year and a half, whose product manifested fetal macrosomia, due to associated complications at the Angela Loayza Obstetric Hospital in Ollague, during the month of February 2020. The The conduct of this study was motivated by the evidence of complications caused by diabetes mellitus in both the mother and the newborn and the high rate of maternal and perinatal morbidity and mortality described worldwide. Objective: For this research work, the objective is to design nursing care plans in a complicated macrosomic newborn through bibliographic reviews and analysis of the newborn's clinical history, to reduce complications in the newborn from the first level of care that is offered to the pregnant woman, avoiding maternal and fetal complications in diabetic women, controlling the level of glycemia and modifiable factors of their daily life that favors the reduction of the incidence of newborns due to fetal macrosomia.
Introducción: La macrosomía fetal es considerada la complicación más frecuente relacionada con la diabetes gestacional, con tasa de morbilidad alta. Según la incidencia a nivel mundial esta alteración representa de 15 a 45% de los recién nacidos de madres diabéticas. se considera macrosómico a todo neonato cuyo peso al nacer sea > 4000 gr, es decir su peso sea igual o mayor al 90 percentil de acuerdo a su edad gestacional. La presente investigación es un estudio de caso clínico en una paciente que presenta diabetes mellitus desde hace 1 año y medio, cuyo producto manifiesto macrosomía fetal, por complicaciones asociadas en el Hospital obstétrico Ángela Loayza de Ollague, durante el mes de febrero del 2020. La realización de este estudio fue motivada por la evidencia de las complicaciones que ocasiona la diabetes mellitus tanto a la madre como al recién nacido y la alta tasa de morbimortalidad tanto materna como perinatal que se describe a nivel mundial. Objetivo: Para el presente trabajo de investigación se plantea como objetivo diseñar planes de cuidados de enfermería en un recién nacidos macrosómico complicado mediante revisiones bibliográficas y análisis de la historia clínica del neonato, para disminuir complicaciones en el recién nacido a partir del primer nivel de atención que se le brinda a la gestante, evitando complicaciones maternas y fetales en mujeres diabéticas, controlando en nivel de glucemia y factores modificables de su vida diaria que favorece a la reducción de la incidencia de recién nacidos por macrosomía fetal.
Keywords: MACROSOMIA; DIABETES MELLITUS; HIPOGLUCEMIA